The client - Grisham, John. (New York : Doubleday & Company, Inc., 1993)
Mark Sway, 11, witnesses a Mafia lawyer's suicide, which puts him in danger from Barry the Blade & a politically ambitious U.S. attorney. In the two years since The Firm first captured the imagination of America's readers, John Grisham, with three consecutive number-one bestsellers, has become one of the most popular authors of our time. Now, in The Client, he has written a novel so irresistible, so thoroughly entertaining and satisfying, that it is sure not only to please his millions of fans, but to win him new ones as well. This is the story of eleven-year-old Mark Sway, who, as the novel opens, witnesses the bizarre suicide of a New Orleans attorney.
Keywords: ATTORNEY AND CLIENT -- WOMEN LAWYERS